2017
DOI: 10.1002/dev.21554
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of maternal and fetal heart rate variability during labor in relation with fetal gender

Abstract: Male gender is considered a risk factor for several adverse perinatal outcomes. Fetal gender effect on fetal heart rate (FHR) has been subject of several studies with contradictory results. The importance of maternal heart rate (MHR) monitoring during labor has also been investigated, but less is known about the effect of fetal gender on MHR. The aim of this study is to simultaneously assess maternal and FHR variability during labor in relation with fetal gender. Simultaneous MHR and FHR recordings were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…The low frequency was addressed in all the 24 articles, where the most common band was within the interval 0.04–0.15 Hz, used in 12 studies, followed by 0.03–0.15 Hz, addressed by 8 articles. Regarding the power in the LF band, most articles attribute it to the activity of the sympathetic system ( 3 , 28 , 31 , 32 , 34 , 49 , 59 , 60 , 62 ), while others link it to the combined activity of sympathetic and parasympathetic activity ( 11 , 13 , 20 , 21 , 44 , 48 , 57 , 61 ). This different interpretation cannot, in some cases at least, be attributed to the different frequency limits of the bands used for the LF computation (check Table 1 ), and is probably inherited by the same controversial interpretation of the LF component in adults' heart rate analysis ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low frequency was addressed in all the 24 articles, where the most common band was within the interval 0.04–0.15 Hz, used in 12 studies, followed by 0.03–0.15 Hz, addressed by 8 articles. Regarding the power in the LF band, most articles attribute it to the activity of the sympathetic system ( 3 , 28 , 31 , 32 , 34 , 49 , 59 , 60 , 62 ), while others link it to the combined activity of sympathetic and parasympathetic activity ( 11 , 13 , 20 , 21 , 44 , 48 , 57 , 61 ). This different interpretation cannot, in some cases at least, be attributed to the different frequency limits of the bands used for the LF computation (check Table 1 ), and is probably inherited by the same controversial interpretation of the LF component in adults' heart rate analysis ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…For cutoff 7.05, although the acidemic group had only 7 subjects, significant differences were found for VLF and LF spectral bands ( Supplementary Table 4 ), and their AUROC were computed ( Table 5 ). Overall, the best AUROC values were: 0.770 for LF 0.03–0.07 Hz ( 49 ); 0.763 for LF 0.02–0.14 Hz ( 62 ) and 0.762 for LF 0.03–0.15 Hz ( 3 , 31 35 , 60 ) (see Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides these factors, Gonçalves et al ( 131 ) and Spyridou et al ( 182 ) noted that gender also has an effect on fHR analysis and should be considered, while Tagliaferri et al ( 183 ) found differences on both linear and non-linear indices between different ethnic groups. Gender was also shown to influence maternal heart rate (MHR) ( 52 ). Even when twins are considered, sex differences were found both by linear and non-linear indices ( 184 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, we found other entropy measures that appeared in less than 15 articles, such as, permutation entropy ( 41 45 ), Rnyi entropy ( 46 48 ), Kullback-Leibler entropy ( 41 , 42 , 49 , 50 ), Kolmogorov-Sinai entropy ( 30 ), cross-sample entropy ( 51 , 52 ), tone-entropy ( 53 ), bubble entropy ( 47 ), and compression entropy ( 46 ).…”
Section: Non-linear Methodsmentioning
confidence: 99%
“…Therefore, findings of these studies cannot be generalized to the whole antepartum period. Moreover, previous studies often examined indices of the FHR that are difficult to reproduce, such as power spectral density (PSD) and approximate entropy (ApEn) [6,7,10,11].…”
Section: Introductionmentioning
confidence: 99%